Innovations in hotel and catering industry - Krilina, A.; Yanenko, Larisa (My University, 2012)
The article emphasizes that service organizations are constantly attempting to find innovative ways to serve customers more efficiently.
Keywords: інформаційні технології; готельна індустрія; розумні системи; информационные технологии; гостиничная индустрия; information technology; hotelindustry; smart systems; кафедра іноземних мов професійного спрямування